Symmetrical electrode material, fuel cell and preparation method thereof
By using Li[NixCo2/3-xMn1/3]O2 as a symmetric electrode material, the problem of insufficient stability and performance of symmetric cells in the prior art is solved, efficient catalytic reactions and good electrical properties are achieved at medium and low temperatures, and the commercial application of solid oxide fuel cells is promoted.
Patent Information
- Application Number
- CN202210463351.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-04-28
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2042-04-28
AI Technical Summary
Existing NCAL-based symmetrical batteries have shortcomings in terms of stability and performance, high operating temperature, low power output and poor stability, which limits the commercial application of solid oxide fuel cells.
Li[NixCo2/3-xMn1/3]O2 (x=1/6,1/3,1/2,2/3) is used as the symmetrical electrode material. This material consists of more stable elements, has excellent catalytic activity and good conductivity, and can maintain high ionic conductivity and good electrical properties at medium and low temperatures.
It realizes efficient catalytic reaction at medium and low temperatures, improves the stability and power output of the fuel cell, reduces the operating temperature, and is cheap in material costs and is easy to industrially produce.
Smart Images

Figure CN114824326B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of solid oxide fuel cells, and in particular to the technical field of solid oxide fuel cells based on symmetrical electrodes. Background Art
[0002] As environmental pollution and energy crisis become increasingly prominent, the research and development of renewable and pollution-free new energy technologies has been put on the agenda. In the field of new energy, fuel cells occupy an important position and are considered to be one of the most promising products to replace traditional fossil energy power generation. In the field of fuel cells, solid oxide fuel cells (SOFCs), as a new type of pollution-free power generation device, have attracted widespread attention due to their unique advantages, including flexible fuel selection, no restrictions on the Carnot cycle, high energy conversion efficiency, no noise, and clean and pollution-free.
[0003] Traditional SOFCs consist of three ceramic components, namely the cathode, anode and dense electrolyte membrane. However, since each component has different functions and its own manufacturing requirements are inconsistent, it poses challenges to the manufacture and commissioning of SOFCs. In order to simplify the manufacturing process, it has become a trend to use the same material to prepare the anode and cathode instead of the traditional method of using different materials to make the anode and cathode, namely symmetric cells (SSOFCs). Compared with traditional electrodes, symmetric electrodes have the advantages of simplifying the manufacturing process, effectively solving the mismatch of thermal expansion coefficients between electrodes and electrolytes, and saving manufacturing costs.
[0004] Nickel-cobalt-aluminum-lithium quaternary oxide Ni 0.8 Co 0.15 Al 0.05 LiO 2-δ (NCAL) has been widely used in the construction of SSOFCs due to its excellent catalytic activity for both hydrogen oxidation and oxygen reduction, and has achieved good battery performance output.
[0005] However, it is often difficult for NCAL-based symmetrical cells to achieve ideal stability. For example, Chen Gang et al. reported that the stability of NCAL-based symmetrical cells was only maintained for 5.8 h (Chen G, Zhu B, Deng H, et al. Advanced Fuel Cell Based on Perovskite La-SrTiO3 Semiconductor as the Electrolyte with Superoxide-Ion Conduction), which is not conducive to the commercialization of SOFC. 0.7 Ca 0.3 Cr 1-y Mn y O3-δ The operating temperature of (y=0.2,0.4,0.6,0.8) series materials needs to be 950℃, and the performance output is only 250mW cm -2 (El-Himri, A, Marrero-Lopez, et al. Structural and electrochemical characterization of Pr0.7Ca0.3Cr1-yMnyO3-d as symmetrical solid oxide fuelcell electrodes); La 0.9 Ca 0.1 Fe 0.9 Nb 0.1 O 3-δ The power density of (LCFNb) at 850°C is only 392 mW cm -2 (Kong X, Zhou X, Tian Y, et al. Niobium doped lanthanum calcium ferriteperovskite as a novel electrode material for symmetrical solid oxide fuel cells). Summary of the invention
[0006] In view of the defects of the prior art, the purpose of the present invention is to provide a symmetrical electrode material and a preparation method thereof. The symmetrical electrode material is composed of more stable elements and has better catalytic activity. It can not only effectively transmit catalytic electrons and ions, but also improve the three-phase reaction interface (TPB), so as to obtain a fuel cell in which each part is tightly combined, the thermal expansion coefficients are matched with each other, and good electrical performance is maintained at medium and low temperatures. Compared with existing symmetrical electrode materials, it has significant advantages in operating temperature, power output, stability, etc.
[0007] The present invention also aims to provide a fuel cell containing the above electrode material and a preparation method thereof.
[0008] The present invention first provides the following technical solution:
[0009] A symmetrical electrode material with the chemical formula: Li[Ni x Co 2 / 3-x Mn 1 / 3 ]O2, where x=1 / 6,1 / 3,1 / 2,2 / 3.
[0010] According to some preferred embodiments of the present invention, the chemical formula of the symmetrical electrode material is: Li(Ni 1 / 3 Co1 / 3Mn 1 / 3 )O2.
[0011] The present invention further provides a method for preparing the above-mentioned symmetrical electrode material, which comprises:
[0012] (1) CoSO4·7H2O and MnSO4·4H2O are mixed and dissolved in deionized water according to a stoichiometric ratio, a Na2CO3 solution is added to the mixed solution, and an ammonia solution is added to adjust the pH to 7-8, and then the mixed solution is heated at a constant temperature of 35-45° C. to obtain a precipitate;
[0013] (2) subjecting the obtained precipitate to solid-liquid separation and washing, and then drying at 110 to 130° C. for 10 to 14 hours to obtain an intermediate product;
[0014] (3) heating the obtained intermediate product at 350-450° C. for 9-11 hours to obtain a decomposition product;
[0015] (4) uniformly mixing the decomposed product with Ni(NO3)2·6H2O and LiNO3 in a stoichiometric ratio, and sintering the mixture at 850-950°C for 10-14h to obtain the symmetrical electrode material;
[0016] Wherein, the stoichiometric ratio satisfies the ratio of each element of the obtained symmetrical electrode material:
[0017] Li[Ni x Co 2 / 3-x Mn 1 / 3 ]O2, x=1 / 6,1 / 3,1 / 2,2 / 3.
[0018] According to some preferred embodiments of the present invention, the stoichiometric ratio of CoSO4·7H2O to MnSO4·4H2O is 1:1, and the intermediate product is Mn 1 / 2 Co 1 / 2 CO3, the decomposition product is Mn 3 / 2 CO 3 / 2 O5.
[0019] According to some preferred embodiments of the present invention, the concentration of the mixed solution in (1) is 1.5 to 2.5 mol / L.
[0020] According to some preferred embodiments of the present invention, the concentration of the Na2CO3 solution in (1) is 1.5-2.5 mol / L.
[0021] The present invention further provides a solid oxide fuel cell containing the above-mentioned symmetrical electrode material or containing the symmetrical electrode material prepared according to the above-mentioned preparation method and a preparation method thereof.
[0022] According to some specific embodiments of the present invention, the preparation method comprises:
[0023] (1) loading the symmetrical electrode material on nickel foam to obtain a Ni-LNCM electrode;
[0024] (2) The Ni-LNCM electrode, the conductor material powder and the Ni-LNCM electrode are molded in this order to obtain the fuel cell.
[0025] According to some preferred embodiments of the present invention, (1) further comprises:
[0026] According to the mass-volume ratio of 1-5 g / ml, LNCM powder and pinene alcohol are mixed and ground to form a uniform slurry, the obtained slurry is evenly applied on the nickel foam, and dried at 110-130° C. for 20-40 minutes to obtain the Ni-LNCM electrode.
[0027] According to some preferred embodiments of the present invention, the conductor material is selected from Ce 0.8 Sm 0.2 O 2-δ and / or BZY.
[0028] The present invention has the following beneficial effects:
[0029] (1) Li[Ni x Co 2 / 3-x Mn 1 / 3 Compared with the lithium ion positive electrode material NCAL in the prior art, the ]O2 (x=1 / 6, 1 / 3, 1 / 2, 2 / 3) material replaces the aluminum element at the B position with the manganese element which has better catalytic activity for hydrogen and is more stable. The symmetrical electrode material of the present invention has excellent comprehensive performance and can obtain high ion conductivity at a relatively low temperature (500-800°C).
[0030] (2) The electrode material of the present invention has excellent mechanical and electrical properties, low price, simple preparation method, high success rate, and is easy to industrialize and produce.
[0031] (3) The fuel cell of the present invention can maintain good electrical performance at medium and low temperatures. The various parts of the battery are tightly combined and the thermal expansion coefficients match each other. In practical operation, problems such as interface cracking caused by changes in internal material stress will not occur.
[0032] (4) In the symmetrical electrode material of the present invention, Li[Ni 1 / 6 Co 1 / 2 Mn 1 / 3 ]O2, Li[Ni 1 / 3 Co 1 / 3 Mn 1 / 3 ]O2, Li[Ni1 / 2 Co 1 / 6 Mn 1 / 3 ]O2, Li[Ni 2 / 3 Mn 1 / 3 ]O2 can be carried on porous nickel foam and can be reduced to nickel-cobalt alloy under reducing atmosphere, which can not only play the role of conducting electrons, but also further improve its ability to catalyze and reduce fuels. Moreover, since it has electronic conductivity and corresponding ionic conductivity, multiple conductivity can expand the three-phase reaction interface and further improve the performance of SOFC based on these materials. At the same time, it has good chemical and thermal compatibility with electrolyte materials and connector materials, low material cost and simple preparation process, and can be used to replace precious metal materials to reduce product costs. At the same time, the symmetrical electrodes made of the same material used as cathode and anode are easy to assemble, which reduces the possibility of mismatch in thermal expansion coefficient between electrodes and electrolyte membranes, and is conducive to commercialization.
[0033] (5) The fuel cell of the present invention exhibits good power output when tested at a temperature of 550°C, and the operating temperature of SOFC can be successfully reduced to 450°C. Further reduction in temperature not only saves costs, but also provides possibilities for further commercialization of solid oxide fuel cells.
[0034] (6) The fuel cell provided by the present invention can operate stably for nearly 50 hours under a fixed current discharge condition without significant voltage decay.
[0035] (7) The electrode material provided by the present invention is applicable to a variety of electrolyte materials. Not only can excellent performance be achieved when SDC is used as the electrolyte membrane to assemble SSOFC, but also it can be used with BaZr 0.5 Y 0.5 Excellent performance can also be achieved when O3(BZY) is used as electrolyte. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] In order to more clearly illustrate the technical solution of the embodiment of the present invention, the drawings of the embodiment are briefly introduced below.
[0037] Figure 1 For different Li(Ni 1 / 3 Co 1 / 3 Mn 1 / 3 )O2XRD spectrum.
[0038] Figure 2 Schematic diagram of the battery structure of the fuel cell described in Example 4.
[0039] Figure 3 This is a performance cooling test chart of the fuel cell described in Example 4 from 550°C to 450°C.
[0040] Figure 4 is the Li(Ni 1 / 3 Co 1 / 3 Mn 1 / 3 ) Thermal expansion curve of O2 from room temperature (29℃) to 800℃ in air atmosphere.
[0041] Figure 5 This is a battery performance test diagram after the electrolyte membrane described in Example 6 is replaced by BZY from SDC.
[0042] Figure 6 The Li[Ni 1 / 6 Co 1 / 2 Mn 1 / 3 ]O2, Li[Ni 1 / 3 Co 1 / 3 Mn 1 / 3 ]O2, Li[Ni 1 / 2Co 1 / 6 Mn 1 / 3 ]O2, Li[Ni 2 / 3 Mn 1 / 3 ]XRD diagrams of four O2 materials.
[0043] Figure 7 : SEM images of the four materials described in Example 7.
[0044] Figure 8 This is a comparison chart of the electrical performance of the battery at 550°C when the four materials described in Example 8 are used as symmetrical electrodes and SDC is used as the electrolyte membrane.
[0045] Fig. 9 This is a stability test diagram of the battery described in Example 3. DETAILED DESCRIPTION
[0046] The present invention is described in detail below in conjunction with the embodiments and drawings, but it should be understood that the embodiments and drawings are only used to exemplify the present invention and do not constitute any limitation on the protection scope of the present invention. All reasonable changes and combinations within the scope of the inventive concept of the present invention fall within the protection scope of the present invention.
[0047] According to the technical solution of the present invention, a specific method for preparing a symmetrical electrode material comprises the following steps:
[0048] (1) CoSO4·7H2O and MnSO4·4H2O are mixed and dissolved in deionized water according to a stoichiometric ratio, 300-400 ml of a 1.5-2.5 mol / L Na2CO3 solution is added to the mixed solution, and an ammonia solution with a concentration of 1.5-2.5 mol / L is added to adjust the pH to 7-8, and then heated in a water bath at 35-45° C. to obtain a precipitate;
[0049] (2) subjecting the obtained precipitate to solid-liquid separation and washing, and then drying at 110 to 130° C. for 10 to 14 hours to obtain an intermediate product;
[0050] (3) heating the obtained intermediate product at 350-450° C. for 9-11 hours to obtain a decomposition product;
[0051] (4) mixing the decomposed product with Ni(NO3)2·6H2O and LiNO3 in a stoichiometric ratio, and sintering the mixture at 850-950°C for 10-14h to obtain the symmetrical electrode material, which is an ABO2 type oxide LNCM;
[0052] Wherein, the chemical formula of the obtained symmetrical electrode material is as follows: Li[Ni x Co 2 / 3-x Mn 1 / 3 ]O2, x=1 / 6,1 / 3,1 / 2,2 / 3.
[0053] Preferably, the chemical formula of the symmetrical electrode material is: Li(Ni 1 / 3 Co 1 / 3 Mn 1 / 3 )O2, the stoichiometric ratio of CoSO4·7H2O and MnSO4·4H2O in step (1) is 1:1, and the intermediate product obtained is Mn 1 / 2 Co 1 / 2 CO3, the decomposition product is Mn 3 / 2CO 3 / 2 O5.
[0054] Preferably, the concentration of the mixed solution in step (1) is 1.5 to 2.5 mol / L.
[0055] Preferably, the concentration of the Na2CO3 solution in step (1) is 1.5 to 2.5 mol / L.
[0056] According to the technical solution of the present invention, a specific method for preparing a fuel cell based on the above-mentioned symmetrical electrode material comprises the following steps:
[0057] (1) obtaining the symmetrical electrode material and the conductor material;
[0058] (2) mixing and grinding LNCM powder and pinene alcohol in a ratio of 2 to 5 g / ml by mass to volume to form a uniform slurry, applying the obtained slurry evenly on the nickel foam, and then drying it at 110 to 130° C. for 20 to 40 minutes to prepare a Ni-LNCM electrode;
[0059] (3) placing a Ni-LNCM electrode, a conductor material powder, and a Ni-LNCM electrode into a mold in sequence, and pressing to obtain the fuel cell;
[0060] Wherein, the conductor material is preferably Sm-doped cerium oxide Ce 0.8 Sm 0.2 O 2-δ That is, SDC and / or BZY.
[0061] According to the technical solution of the present invention, the following is further demonstrated in combination with the embodiments:
[0062] Example 1
[0063] ABO2 type oxide LNCM was prepared by the following process:
[0064] (1) CoSO4·7H2O and MnSO4·4H2O powders with a stoichiometric ratio of 1:1 were mixed and dissolved in deionized water to form a mixed solution with a solute concentration of 2 mol / L, and then 2 mol / L Na2CO3 solution was uniformly added to the obtained sulfate mixed solution to form a purple precipitate, 5 g of 20% ammonia water was weighed, 343 ml of deionized water was added, and the mixture was stirred to form a 0.24 mol / L ammonia solution, and the ammonia solution was slowly added dropwise to the mixed solution to adjust the pH value, and the pH value of the solution was controlled at 7.5, and the mixed solution was placed on a stirrer at a temperature of 40°C and a speed of 800 r / min and stirred for 4 h;
[0065] (2) filtering the precipitate obtained in step (1) and rinsing it twice with deionized water to remove residual Na2CO3;
[0066] (3) The obtained precipitate was placed in a forced air drying oven at 120°C for 12 hours to obtain the intermediate product Mn 1 / 2 Co 1 / 2 CO3;
[0067] (4) The intermediate product was placed in a muffle furnace and heated at 400°C for 10 h. 1 / 2 Co 1 / 2 CO3 is completely decomposed into Mn 3 / 2 CO 3 / 2O5;
[0068] (5) The obtained Mn 3 / 2 Co 3 / 2 O5, Ni(NO3)2·6H2O and LiNO3 were mixed in a molar ratio of 2:3:9, and the mixture was sintered in a muffle furnace at 900°C for 12 h to obtain the final product Li(Ni 1 / 3 Co 1 / 3 Mn 1 / 3)O2 (hereinafter referred to as LNCM).
[0069] The obtained LNCM powder was characterized by XRD. Figure 1 As shown in the figure, it can be found that the obtained LNCM peak is sharp and has no impurity peaks, indicating that the synthesized LNCM has high crystallinity, no other impurities and a layered structure.
[0070] Example 2
[0071] The symmetric electrode was prepared by the following process:
[0072] According to the ratio of mass to volume of 3:1, for example, 3g of the LNCM powder obtained in Example 1 corresponds to 1ml of pinene alcohol, the LNCM powder and pinene alcohol are mixed evenly in a grinding mortar and ground for 15 minutes to form a uniform slurry. The obtained slurry is evenly applied on a 2mm thick nickel foam, which is then placed in a blast drying oven set at 120°C for 30 minutes to prepare a Ni-LNCM electrode.
[0073] Example 3
[0074] Solid oxide fuel cell green sheets are prepared by the following process:
[0075] Weigh 0.3 g of SDC powder, put the Ni-LNCM electrode, SDC, and Ni-LNCM electrode obtained in Example 2 into a special mold in sequence, and use a hydraulic press to apply a pressure of 10 MPa for 2 minutes to press the three-layer structure into a battery sheet.
[0076] Example 4
[0077] Battery performance test:
[0078] The solid oxide fuel cell embryo obtained in Example 3 was placed at a test temperature of 550°C, and hydrogen and air were introduced into the two sides of the symmetrical electrodes, respectively. Figure 2 As shown, the hydrogen and air flow rates were controlled at 150mL / min and 130mL / min to test the battery performance, and the open circuit voltage and power of the battery were recorded. The same battery was tested at a temperature drop from 550℃ every 20 degrees. The results are shown in the attached figure. Figure 3 As shown in the figure, it can be seen that the obtained battery has a high power output, and the output power density can reach 815mW / cm at 550℃ 2 As the temperature decreases, the power density also decreases. This is because the conductivity of the electrolyte membrane and the catalytic activity of the electrode also decrease as the temperature decreases. It can be seen that even if the temperature drops to 450°C, the battery provided by the present invention can still maintain nearly 200mW / cm 2 power density.
[0079] Example 5
[0080] Thermal Expansion Coefficient Test:
[0081] 1 g of the LNCM powder obtained in Example 1 was weighed into a special mold, and a pressure of 6 MPa was applied to press it into a cylindrical shape. After being placed in a muffle furnace set at a temperature of 800 ° C for 4 h, the thermal expansion coefficient was measured using a thermal expansion instrument. The test temperature was from room temperature to 800 ° C, and the heating rate was controlled at 10 ° C / min. The results are shown in the attached figure. Figure 4 As shown. It can be seen that under the same conditions, the average thermal expansion coefficient of LNCM is 12.45×10 -6 K -1 , which is consistent with the thermal expansion coefficient of SDC reported in the literature of 12.28×10 - 6 K -1 In comparison, the thermal expansion coefficients of the two match, which can be used to explain the lack of cracks between the electrode and the electrolyte membrane.
[0082] Example 6
[0083] Battery performance test when the electrolyte is replaced by BZY from SDC:
[0084] 0.3 g of BZY powder was weighed as the electrolyte, and the symmetrical electrode was still LNCM. The same method as in Example 3 was used to press the battery embryo sheet. The same method and conditions as in Example 4 were used to perform the performance test. The results are shown in the attached figure. Figure 5 shown.
[0085] It can be seen that when the electrolyte is replaced by SDC with BZY, the battery can still maintain 475mW / cm 2 The power density of LNCM provided by the present invention is 1.34 W, which proves that the electrode material provided by the present invention is compatible with a variety of electrolytes. At the same time, since BZY is a pure proton conductor and SDC is a pure oxygen ion conductor, the battery can maintain excellent power output when the two materials are used as electrolyte membranes, which proves that the electrode material LNCM provided by the present invention has good catalytic activity for both hydrogen and air.
[0086] Example 7
[0087] The same synthesis method as in Example 1 was used, but the value of the molecular formula x was different, and the molar ratio of the raw materials Ni(NO3)2·6H2O and CoSO4·7H2O was controlled to synthesize Li[Ni 1 / 6 Co 1 / 2 Mn 1 / 3 ]O2, Li[Ni 1 / 3 Co 1 / 3 Mn 1 / 3 ]O2, Li[Ni 1 / 2 Co1 / 6 Mn 1 / 3 ]O2, Li[Ni 2 / 3 Mn 1 / 3 ]O2 four kinds of materials. The XRD and SEM spectra of the four materials are shown in the attached Figure 6 and 7 shown.
[0088] It can be seen that the XRD patterns of the four materials are the same as a whole, and there are no impurity peaks. However, as the nickel content at the B position increases, the XRD peak gradually shifts to the left as a whole. The reason includes that the ionic radius of nickel is larger than the atomic radius of cobalt, resulting in the increase of nickel content and the larger lattice constant of the material, and the overall leftward shift of the peak appears in the XRD pattern.
[0089] It can be clearly seen from the SEM images of the four materials that their original microstructures are all spherical, and except for Li[Ni 1 / 2 Co 1 / 6 Mn 1 / 3 ]O2, the other three materials are Li[Ni 1 / 6 Co 1 / 2 Mn 1 / 3 ]O2, Li[Ni 1 / 3 Co 1 / 3 Mn 1 / 3 ]O2, Li[Ni 2 / 3 Mn 1 / 3 ]O2 are all irregular spherical.
[0090] Example 8
[0091] The four materials synthesized in Example 7 were respectively made into symmetrical electrodes and symmetrical batteries according to the steps of Examples 2 and 3, and then the performance tests were respectively carried out according to the battery performance test method of Example 4. All test temperatures were set at 550° C. The results are shown in the attached figure. Figure 8 shown.
[0092] It can be seen that with the increase of nickel in the B site and the decrease of cobalt, the performance of the battery first increases and then decreases. Specifically, when the value of x is from 1 / 6 to 1 / 2, the performance of the symmetrical battery gradually increases, but when x is 2 / 3, the performance decreases instead.
[0093] It can be seen that Li[Ni 1 / 2 Co 1 / 6 Mn 1 / 3 The output power density of the symmetrical solid oxide fuel cell can reach 923mW / cm 2 This is not only better than the other three electrode materials, but also far better than the performance of symmetrical batteries when NCAL is used as a symmetrical electrode under the same conditions.
[0094] Example 9
[0095] Stability test:
[0096] When Li[Ni 1 / 3 Co 1 / 3 Mn 1 / 3 ]O2 is used as the symmetrical electrode and SDC is used as the electrolyte membrane. The battery embryo is pressed into a battery embryo by the method of Example 3, wherein the applied pressure is increased to 11MPa, and the battery embryo is preheated at 550℃ for 1h before the stability test. The performance test steps of Implementation 4 are adopted, but the performance test is not performed. When the voltage rises to the maximum value and is stable for more than 10min, it can be tested at 100mAcm -2 The battery is discharged at a fixed current, and the battery maintenance level and duration are observed and recorded. The results are shown in the attached figure. Fig. 9 As shown. It can be seen that after nearly 50 hours of continuous discharge, the battery voltage provided by the present invention still has no obvious attenuation, indicating that during the long-term test process, the electrode and electrolyte materials are stable, without reaction and decomposition, and conversion into other substances. The electrode and electrolyte are also stable with each other, and the two do not react. Stability is one of the key indicators of SOFC and largely determines the degree of commercialization of SOFC.
[0097] The above embodiments are only preferred implementations of the present invention, and the protection scope of the present invention is not limited to the above embodiments. All technical solutions under the concept of the present invention belong to the protection scope of the present invention. It should be pointed out that for ordinary technicians in this technical field, improvements and modifications without departing from the principle of the present invention should also be regarded as the protection scope of the present invention.
Claims
1. A method for preparing a solid oxide fuel cell containing symmetrical electrode materials: characterized in that: The chemical formula of the symmetrical electrode material is Li[Ni 1 / 2 Co 1 / 6 Mn 1 / 3 ]O 2; The preparation method of the symmetrical electrode material comprises: (1) CoSO4⋅7H2O and MnSO4⋅4H2O are mixed and dissolved in deionized water according to a stoichiometric ratio, a Na2CO3 solution is added to the mixed solution, and an ammonia solution is added to adjust the pH to 7-8, and then the mixture is heated at a constant temperature of 35-45°C to obtain a precipitate; (2) After solid-liquid separation and washing, the obtained precipitate is dried at 110-130° C. for 10-14 hours to obtain an intermediate product; (3) heating the obtained intermediate product at 350-450°C for 9-11 hours to obtain a decomposition product; (4) uniformly mixing the decomposed product with Ni(NO3)2⋅6H2O and LiNO3 in a stoichiometric ratio, and sintering the mixture at 850-950°C for 10-14h to obtain the symmetrical electrode material; Wherein, the stoichiometric ratio satisfies the ratio of each element of the obtained symmetrical electrode material: Li[Ni x Co 2 / 3-x Mn 1 / 3 ]O2, x=1 / 2; The concentration of the mixed solution in (1) is 1.5-2.5 mol / L; The concentration of the Na2CO3 solution in (1) is 1.5-2.5 mol / L; The method for preparing the solid oxide fuel cell comprises: 2-1: Loading the symmetrical electrode material on nickel foam to obtain a Ni-LNCM electrode; 2-2: molding the Ni-LNCM electrode, the conductor material powder, and the Ni-LNCM electrode in this order to obtain the fuel cell; Wherein, the above 2-1 further includes: Mixing and grinding the powder of the symmetrical electrode material with pine alcohol in a ratio of 1 to 5 g / ml by mass and volume to form a uniform slurry, applying the obtained slurry evenly on the nickel foam, and drying it at 110 to 130° C. for 20 to 40 minutes to obtain the Ni-LNCM electrode; The conductor material is selected from Ce 0.8 Sm 0.2 O 2-δ and / or BaZr 0.5 Y 0.5 O3.